Using videos to assess preference for novel stimuli in children with autism. (17th November 2017) - Brodhead, Matthew T.; Rispoli, Mandy J.
ABSTRACT: A primary effort of preference assessment research has been to develop strategies to identify potential reinforcers for educational, social, and behavioral programming for individuals with disabilities, including children with autism. However, little attention has been paid to the identification of preferred stimuli children with autism may not have previous experience with. The purpose of this study was to evaluate the extent to which a video-based preference assessment may accurately identify preference for novel stimuli. We compared the results of the video-based preference assessment with no access to novel stimuli to the results of a preference assessment conducted in a tangible format with access. We then conducted the same video-based preference assessment a second time to evaluate the extent to which exposure to stimuli affected assessment results. The results provide preliminary support that a video-based preference assessment may accurately identify preference for novel stimuli. Implications and future directions are discussed.